Nanorobots in Targeted Drug Delivery System – A General Review - mishbahurroyan1, nazhifah; faadhilah rizki winarno, noor; ikbar nafis, sandy; valdino, yosafat; listyorini, niken (Liaison Journal of Engineering, 2023)
A targeted drug delivery system is a method for accurately administering the drug component to a targeted area of the body (such as an organ, cellular level, or subcellular level of a specific tissue), with the goal of avoiding the non-specific adverse effects linked to conventional drug delivery [1]. The presence of targeted drug delivery systems allows the reduction of cytotoxic drugs overall toxicity, reducing side effects, while improving the efficacy and selectivity of the drugs [2]. This strategy eventually leads to a decrease in the amount of medication required to achieve therapeutic efficacy. This method is especially beneficial in the treatment of several diseases, such as cancer, because unlike chemotherapy that often results in the death of all rapidly proliferating cells in order to eradicate tumor or cancerous cells, the majority of targeted therapy approaches work to treat cancer by disrupting particular proteins that aid in the growth and metastasis of tumors in the body [3]. This in turn improves therapy effectiveness and decreases undesirable side effects. Side effects occur as a result of cancer treatment including pain, fatigue, anemia, and hair, skin, and nail problems [4]. The field of study of nanorobotics is an emerging field of study with a revolutionary potential in various areas, including biomedicine [5]. The application of nanorobots in targeted drug delivery systems, especially as therapeutic agents carriers aids in the succession of targeted drug delivery systems. This journal discusses the topic of nanorobots in the Targeted Drug Delivery System, spotlighting its fabrication, applications, limitations, and future direction. In addition, general knowledge regarding nanorobots profile is fundamental in the comprehension of its applications, hence the provision of sections ‘Nanorobots profile’. Keywords: Targeted drug delivery, Nanorobots, Propulsion Type, Pharmaceutical drugs, Top-down and bottom-up approaches, Precision control, Biologics, Biocompatibility, Scalability